Reflexões sobre a série “Musas Inquietantes” - Revisitando 1994 de Alphonsus Benetti - Brasil, Luana de Siqueira (2012)
This work was developed in the research line Art and Visuality of the Masters in Visual Arts at the Universidade Federal de Santa Maria. This research presents a of the series "Musas Inquietantes - Revisitando 1994 by Alphonsus Benetti. The eight paintings in the series have transitioning characteristics from modern to contemporary. From this point of transition it was sought a better understanding of the artistic context experienced by Alphonsus Benetti. Considering the subject and the objectives set out for this research, it was decided to carry a Case Study of a qualitative nature of interpretive, descriptive and reflective levels. In the first chapter, a few debates that occurred within the modernism, and also, the contribution of these contradictions for contemporary art are pointed out. In the second chapter, it is presented how the artist approached the world of arts and his artistic path, which resulted in 38 years dedicated to the arts. In the end, there is a reflection on the series "Musas Inquietantes - Revisitando 1994 by Alphonsus Benetti.